The Effect Of Esg Disclosure, Asset Turnover, And Working Capital Turnover On Financial Performance In Industrial Goods Companies Listed On The Indonesian Stock Exchange From 2021 To 2024 - Abdurrahman Faiz Ghifari; Retno Yulianti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) disclosure, Asset Turnover (TATO), and Working Capital Turnover (WCTO) on the financial performance of industrial companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2024. This study uses a quantitative approach with a comparative causal research design. The data used is secondary data obtained from companies' annual financial reports and sustainability reports. Sampling was determined using purposive sampling, resulting in 113 observations that met the research criteria. The analysis method used was multiple linear regression to test the effect of independent variables on financial performance, which was proxied by Return on Assets (ROA). The results showed that ESG disclosure and asset efficiency had an effect on the financial performance of industrial companies, while working capital management efficiency showed varying effects. This study contributes to enriching the financial accounting literature by integrating aspects of sustainability and operational efficiency, as well as providing practical implications for company management, investors, and regulators in making sustainability-oriented decisions.